Cyclogenesis over the Aegean Sea: Identification and synoptic categories - H. A. Flocas; Karacostas, T.S. (Meteorological Applications, 1996)
An attempt is made to identify and investigate the structure, behaviour and synoptic characteristics of cyclogenesis over the Aegean Sea. A simple, realistic and easily used methodology of identification, in an analytical form, was established. This combines two types of criteria: synoptic and dynamic/thermodynamic. Six synoptic categories that could favour cyclogenesis over the Aegean Sea are distinguished according to the synoptic criteria. Grid-point values of geopotential height and temperature are used to calculate the dynamic/thermodynamic criteria, which are used to identify potential cases of cyclogenesis with respect to the thermodynamic prerequisites and the time continuance. It is demonstrated that cyclogenesis over the Aegean Sea is not as rare as was believed. The majority of cases result from the prevalence of a south-westerly flow, a long-wave trough and a closed system over the Aegean Sea. The cyclogenesis appears to occur primarily in the cold period of the year, mainly from October to May, and to have a small intensity and lifetime.